Thermal Model of Calcite Calcination Process - V. А. Sednin; A. G. Kozhevnikov; I. V. Melnikov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The purpose of the paper is to develop thermal model of heat conduction in a piece of СаСОз raw material. The proposed model makes it possible to reconsider the parameters of calcination process in favor of fuel rate decrease.